SCIENTIFIC VALIDATION AND STANDARDIZATION OF PARPATAKA AN AYURVEDIC DRUG WITH RESPECT TO FUMARIA INDICA - JYOTHI, B.; PRATAP, GOLI PENCHALA; HUSAIN, MOHD KASHIF; KAZMI, MUNAWWAR HUSSAIN; PRASAD, G. P.; SUDARSANAM, G. (International Journal of Current Pharmaceutical Research, 2019)
Objective: Fumaria indica is an essential curative herb and asserted as a prevalent weed across the plains of India. The entire plant is popularly employed in conventional systems of medicine for its therapeutic activities like anthelmintic, diuretic, diaphoretic, laxative, purging and stomachic. The entire plant is regarded to have therapeutical purposes in Ayurvedic and Unani systems of medicine and is employed in the preparation of important Ayurvedic formulation Parpataka. In Unani systems of medicine, it is used as shahtara. This contemporary study is intended to authenticate and validate the species Fumaria indica with respect to Parpataka drug. Methods: The chief objective of this contemporary research work is to assess the various pharmacognostic properties like Macroscopical, Microscopical, Physiochemical and Fluorescence studies. Microscopical studies include cell structure and their arrangement, Physicochemical parameter s include loss on drying, total ash value, acid insoluble ash, water-insoluble ash, various extractive values etc. Qualitative tests for various functional groups were also carried out. Results: The microscopical characters of leaf, stem and roots, physicochemical, preliminary phytochemical profiles were established. Conclusion: The pharmacognostical screening on Fumaria indica is significant data for the identification and to determine the quality and purity of the plant material in future reviews.